Ezekiel’s Spirit Motif in the Context of African Pentecostal Theology - Omondi, Francis (Stellenbosch Theological Journal, 2026)
In Ezekiel’s Spirit Motif in the Context of African Pentecostal Theology, Samuel Muindi responded to a lacuna in biblical scholarship a hermeneutic of the African “spirit” worldview and the African Pentecostal pneumatology in particular (1). Muindi interprets Ezekiel’s spirit motif in the African Pentecostal theology in Africa’s “en-spirited” worldview and relates Ezekiel’s spirituality represented by the imageries and symbolism of spirit’s experience to the African Pentecostal spirituality. He points to African peoples’ contextual construct of divine presence in an African spirit worldview. Muindi associates the African spirit worldview with the Pentecostal-Charismatic movement pneumatology, the African Christianity considered a syncretistic blend of Western Christianity and African traditional beliefs. However, he contends, African Christianity is a contextual faith and not as syncretistic as it appears.